2020
DOI: 10.21203/rs.3.rs-17647/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Upregulation of long non-coding RNA LOC284454 may serve as a new serum biomarker for head and neck cancers

Abstract: Purpose: Identification of effective diagnostic and prognostic biomarkers of cancer is necessary for improving precision medicine. Long non-coding RNAs(lncRNAs) play an important regulatory role in tumorinitiation and progression. The lncRNA LOC284454 is distinctly expressed in various head and neck cancers(HNCs), as demonstrated by our previous bioinformatics analysis. However, the expression levels and functions of LOC284454 in cancer are still unclear.Methods: We investigated the dysregulation of lncRNAs in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Recently accumulated evidence has suggested that lncRNA may play an important role in cell biology and human disease. In gynaecological cancer, several lncRNAs were identified, including HOTAIR, SRA, MALAT-1, H19 and LSINCT5 [17][18][19][20]. On the basis of these data, lncRNA is emerging as an early diagnosis and treatment target.…”
Section: Discussionmentioning
confidence: 99%
“…Recently accumulated evidence has suggested that lncRNA may play an important role in cell biology and human disease. In gynaecological cancer, several lncRNAs were identified, including HOTAIR, SRA, MALAT-1, H19 and LSINCT5 [17][18][19][20]. On the basis of these data, lncRNA is emerging as an early diagnosis and treatment target.…”
Section: Discussionmentioning
confidence: 99%